(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This article explores the relationship between science, technology, and art in an Islamic view, emphasizing religious attitudes and perspectives on the advancement of human thought and creativity. This study uses a literature study method. Information is obtained from literature reviews that include various sources such as academic journals, online articles, and relevant case studies. The analysis was carried out thoroughly on the data that had been collected, with an emphasis on the relevance of the information to the main theme of the writing. The results obtained from this study are that the application of science, technology, and art in daily life in accordance with Islamic teachings can create a balance between spiritual and material aspects, bring happiness in this world and the hereafter, and make a significant contribution to building a better human civilization.